"I Am You and You Are Me": A Self Psychology Perspective on Sibling Relationships. Issue 1 (2nd January 2021) - Hart, Claire
Abstract: Vertical and lateral functions shape one's sense of self and help one understand their place in the world. Yet, there are significant gaps in self psychology regarding the subjective aspects of self-sustaining functions provided by siblings and how these may differ from parental functions. This article examines these concepts from the perspective of a volunteer group of six adult participants who had high-access parent and sibling relationships in childhood. The analysis of eighteen psychoanalytic interviews showed that siblings can function as more than reparative or replacement vertical figures. As the participants' parents were subjectively experienced as present and good enough at offering specific vertical functions, this article outlines some of the distinctive lateral functions that can be fulfilled by siblings, including idealizing and twinship. Further theoretical and clinical engagement with vertical and lateral functions is necessary in order to deepen self-psychological understandings of parent and sibling relationships.